Human herpesvirus 7: antigenic properties and prevalence in children and adults. - Wyatt, L S (1991)
The recent isolation of human herpesvirus 7 (HHV-7) from activated CD4+ T lymphocytes of a healthy individual raises questions regarding the prevalence of this virus in humans and its immunological relationship to previously characterized human herpesviruses. We report that HHV-7 is a ubiquitous virus which is immunologically distinct from the highly prevalent T-lymphotropic HHV-6. Thus, (i) only two of six monoclonal antibodies to HHV-6 cross-reacted with HHV-7-infected cells, (ii) Western immunoblot analyses of viral proteins revealed different patterns for HHV-6- and HHV-7-infected cells, (iii) tests of sequential serum samples from children revealed seroconversion to HHV-6 without concomitant seroconversion to HHV-7, and (iv) in some instances HHV-7 infection occurred in the presence of high titers of HHV-6 antibodies, suggesting the lack of apparent protection of children seropositive for HHV-6 against subsequent infection with HHV-7. On the basis of the analyses of sera from children and adults it can be concluded that HHV-7 is a prevalent human herpesvirus which, like other human herpesviruses, infects during childhood. The age of infection appears to be somewhat later than the very early age documented for HHV-6.